Photoluminescence in quasi-amorphous Pb0.8X0.2Zr0.53Ti0.47O3 (X = Ca, Sr and Ba) powders: An optical and structural study - Longo, V. M. [UNESP]; Silva, M. S.; de Figueiredo, A. T. [UNESP]; Franco, R. W. A.; Vila, C. [UNESP]; Cilense, M. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Andres, J. (Elsevier B.V., 2009)
Crystalline and quasi-amorphous PZT and PZT:X (X = Ca, Sr and Ba) powders were obtained by the polymeric precursor method. Electron paramagnetic resonance (EPR) and photoluminescence (PL) data suggest that the presence of order-disorder within the lattice network, i.e., the appearance of symmetry-breaking processes that give rise to non-ideal octahedra and networks of dodecahedral clusters, is an essential factor for the occurrence of PL. Measurements of PL indicate that the shallow defects in the band gap enhance blue light emission. (c) 2009 Elsevier B.V. All rights reserved.